(untitled) (Annals of Medical Research, 2022)
Aim: Low back pain is pain, muscle tension, or stiffness localized below the costal margin and above the inferior gluteal folds, with or without leg pain (sciatica), and is defined as chronic when it persists for 12 weeks or more. Several studies have addressed the relationship between chronic low back pain and poor sexual activity for over two decades. This study was designed to clarify the relationship between depression and chronic low back pain in light of the information obtained from the literature review and examine how it affects sexual life. Materials and Methods: Eighty people participated in the study. After signing the informed consent form, participants were examined by experienced physicians. Quebec Low Back Pain Scale, Beck’s Depression Scale, and Arizona Sexual Experiences Scale (ASEX) were applied to the participants. Results: As a result of the Mann-Whitney U test, which examined whether there was a significant difference in the Arizona Sexual Experiences Scale scores between the case group and the control group, there was a significant difference between the groups (U=256,500, p<.001). When the mean ranks were examined, it was seen that the case group had a higher ASEX score than the control group. In our study, it was found that there was a significant difference between the groups as a result of the Mann-Whitney U test, which was carried out to examine whether there was a significant difference between the Quebec score points between the case group and the control group. (U=30,000, p<.001). Conclusion: In our study, it was observed that chronic low back pain significantly increased the level of depression and paved the way for functional losses in sexual terms. There is a moderate correction between a higher Quebec score and lower sexual satisfaction. It was found that there was a moderate relationship between Beck’s depression score and sexual satisfaction. The 33-42 age group has higher Quebec scores than other age groups. It was found that there was no significant difference in scores between the groups according to gender, license degree, and marital status.